2021
DOI: 10.3390/clockssleep3030034
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of General Anaesthesia and Light on Behavioural Rhythms and GABAA Receptor Subunit Expression in the Mouse SCN

Abstract: General anaesthesia (GA) is known to affect the circadian clock. However, the mechanisms that underlie GA-induced shifting of the clock are less well understood. Activation of γ-aminobutyric acid (GABA)-type A receptors (GABAAR) in the suprachiasmatic nucleus (SCN) can phase shift the clock and thus GABA and its receptors represent a putative pathway via which GA exerts its effect on the clock. Here, we investigated the concurrent effects of the inhalational anaesthetic, isoflurane, and light, on mouse behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…General anesthesia has profound effects on the neurotransmitter systems, primarily those mediated by GABA, that regulate the circadian clock. Anesthetic agents such as isoflurane have been shown to exert a phase-shifting effect on the clock by activating SCN GABA receptors ( Chong et al, 2021 ). Furthermore, anesthesia alters the expression of several core clock genes, notably PER2 .…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…General anesthesia has profound effects on the neurotransmitter systems, primarily those mediated by GABA, that regulate the circadian clock. Anesthetic agents such as isoflurane have been shown to exert a phase-shifting effect on the clock by activating SCN GABA receptors ( Chong et al, 2021 ). Furthermore, anesthesia alters the expression of several core clock genes, notably PER2 .…”
Section: Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…This combination of anaesthetics was selected so as to maintain a stable surgical plane and thereby reduce the modulating influence of the general brain state on the LGN neuronal activity (Jeczmien‐Lazur et al., 2019). This was based on previous reports that suggested that deep anaesthesia may shift the phase of internal circadian timekeeping (Chong et al., 2021; Ludin et al., 2021; Prudian et al., 1997). Although the exact mixture of anaesthetics we used has not yet been tested for its hypothetical effects on the circadian clock, it is known that other general anaesthetics with similar effects (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mixture of anaesthetics we used has not yet been tested for its hypothetical effects on the circadian clock, it is known that other general anaesthetics with similar effects (e.g. isoflurane, ether, halothane, or ketamine administered in combination with benzodiazepines) differentially affect circadian rhythms in rodents (Bellet et al., 2011; Chong et al., 2021; Ludin et al., 2021; Mihara et al., 2012; Prudian et al., 1997; Rebuelto et al., 2004). Moreover, our observations show that even minimal changes in the slow‐wave activity amplitude may affect the level of neuronal activity, and that, in turn, could influence the amplitude of the responses.…”
Section: Resultsmentioning
confidence: 99%